Zoning and Evaluation of Geological Disaster Vulnerability Based on Multi-source Data Integration in Loess Area of East Gansu --Taking Xifeng District as an Example. Issue 7 (April 2020) - Hu, Aiping; Wang, Yun
Abstract: Xifeng District, Qingyang City, Gansu Province is located in the hinterland of Dongzhi tableland in the East Gansu Loess Plateau. The common geological disasters in here are landslides, unstable slopes, and debris flows. From the multi-source data, 14 factors with obvious influence are selected to constitute the index system, and the weight of each factor is obtained by using the AHP method. Based on the multi-source data integration method, the 14 factors are superimposed to obtain the geological hazard-prone zoning and evaluation in this area. The evaluation results show that the area is divided into 3 areas prone to geological disasters, and 9 sub-areas. (1) The high-prone area accounts for 48.96% of the total area, and the geological disasters mainly are unstable slopes. (2) The medium-prone area accounts for 22.64% of the total area. (3) The low-prone area accounts for 28.4% of the total area. The results not only provide a theoretical and practical basis for the establishment of a geological hazard assessment system in the East Gansu Loess Region, but also provide an important basis for the urban planning development and environmental coordination in Qingyang City.